Serological and molecular evaluation of Senecavirus A (SVA) in pigs from farrow-to-finish farms in Minas Gerais, Brazil - Júnio César Santos; Emelly Barbosa Calheiros; Leonardo Teófilo Toledo; Ugonna Henry Uzoka; Fernanda Simone Marks; Wagnner José Nascimento Porto; Alessandra Abel Borges; João Alberto Farinelli Pantaleão; Maria Isabel Isabel Maldonado Coelh Guedes; Carlos Eduardo Real Pereira; David Germano Goncalves Schwarz; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2026)
The emergence of Senecavirus A (SVA) as a causative agent of vesicular diseases in pigs is noteworthy, since it was identified in 2014 through outbreaks in Brazil. The SVA belongs to the Picornaviridae family and is a non-enveloped virus with the ability to adapt to the environment. As the virus’s stability allows it to persist on farms post-outbreak, maintaining stringent biosecurity measures is crucial for effective control. This study aims to evaluate antibody response and viral RNA shedding in swine farms. Blood and fecal samples were collected from pigs in 2022 on farms that experienced outbreaks in 2015 and 2016. The sampled pigs were from farrow-to-finish farms without clinical signs of SVA obtained from five farms in Minas Gerais state, Brazil, covering all production phases: sows, farrowing, nursery piglets, growing, and finishing pigs. Real-time PCR and serum neutralization tests were conducted. Antibodies against SVA were detected in all production phases from four of the positive farms, with sows showing the highest antibody prevalence. Viral RNA was found in fecal samples from two farms, with the farrowing phase pigs exhibiting the highest viral RNA positivity. These findings indicate the presence of SVA infection on farms with no clinical signs, suggesting that the virus may have persisted following previous outbreaks due to its environmental stability. This study provides a comprehensive profile of antibody and viral RNA presence across different production phases, which may be applicable for informing biosafety measures.

Micro- and nanoplastics as emerging disruptors of Leydig cell function: A systematic review of experimental evidence - Isabel Ochando; Laura Compañ-Gabucio; Antonio Urbano; Mariano Andrés; Javier Marco-Lledó; Vanessa Zorrilla-Muñoz; Javier Hernández-Borges; Pilar Madrigal-Verdú; Jonatan García-Campos; Nicanor Morales-Delgado; Gema Martínez-Navarrete (Environmental Toxicology and Pharmacology, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Influence of refuge availability on the oviposition strategy of anachoretic and non-anachoretic aphidophagous ladybirds - António Onofre Soares; Marta Vale; Isabel Borges; Eric Lucas (BioControl, 2025)
Scymnus nubilus Mulsant and Coccinella undecimpunctata L. (Coleoptera: Coccinellidae) are two generalist aphidophagous predators abundant in herbaceous habitats. C. undecimpuctata , a larger species, lays its eggs in uncovered clusters, whereas S. nubilus , a tiny species , lays its eggs singly and, possibly, in concealed sites. Reproductive strategies in ladybirds seem to be adaptive, allowing the co-occurrence of both predators, apparently without interfering with each other. The aim of this study was to characterize the following oviposition strategies in S. nubilus and C. undecimpunctata : daily fecundity, effect of available sites on females’ fecundity, and circadian rhythmicity of oviposition. We hypothesize that the single-egg-laying strategist (1) is more dependent on the availability of concealed sites to oviposit and (2) lays eggs closer to aphid colonies. We found that different levels of site concealability allows S. nubilus to increase fecundity. Contrary to C. undecimpunctata , in the absence of a suitable substrate to conceal its eggs, S. nubilus females refrain ovipositing. S. nubilus prefers to hide their eggs beneath prey carcasses while C. undecimpunctata is less selective concerning the oviposition sites. S. nubilus dilutes its fecundity effort through more oviposition sites and events, while C. undecimpunctata requires one event to lay its clusters. Our results showed that the smaller ladybird is more dependent than the larger one on habitat structural complexity to maximize its fitness and that laying a single hidden egg mainly during the scotophase confers a potential adaptive advantage to increase fitness.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Threats and conservation status of the endemic terrestrial arthropods of the Azores - Guilherme Oyarzabal; Gabor Pozsgai; Noelline Tsafack; Pedro Cardoso; François Rigal; Mário Boieiro; Ana M.C. Santos; Isabel R. Amorim; Jagoba Malumbres-Olarte; Ricardo Costa; Sébastien Lhoumeau; Rosalina Gabriel; et al. (Biological Conservation, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

First isolation of Leptospira interrogans from follicular fluid of naturally infected cows - Ana Luiza dos Santos Baptista Borges; Luiza Aymée; Isabel Roussouliéres; Filipe Anibal Carvalho-Costa; Maria Isabel Nogueira Di Azevedo; Walter Lilenbaum (Veterinary Microbiology, 2025)

Ephestia kuehniella Zeller eggs as a surrogate host to test feeding preference and intraguild interactions between Macrolophus pygmaeus (Rambur) and Trichogramma achaeae Nagaraja and Nagarkatti - António O. Soares; Ana C. Durão; Luisa Oliveira; Patrícia Arruda; Isabel Borges (Crop Protection, 2025)

Molecular epidemiology of Leptospira spp. serogroup Sejroe associated with chronic bovine leptospirosis - Ana Luiza dos Santos Baptista Borges; Luiza Aymée; Filipe Anibal Carvalho-Costa; Walter Lilenbaum; Maria Isabel Nogueira Di Azevedo (Veterinary Microbiology, 2024)

Proposal for a social certification model for agriculture in Latin America aligned with the sustainable development goals - Javier Eugenio García de Alba Verduzco; Samuel Borges Barbosa; Blanca Catalina Ramírez Hernández; Leila Dal Moro; Luis Enrique Lomelí Rodríguez; Luciana Londero Brandli; André Borchardt Deggau; Maria Gabriela Mendonça Peixoto; Angélica Isabel García Navarro; Simone Sehnem; Viviane dos Guimarães Alvim Nunes; José Baltazar Salgueirinho Osório de Andrade Guerra (Environment, Development and Sustainability, 2024)

Type III sourdough: Evaluation of biopreservative potential in bakery products with enhanced antifungal activity - Lílian Borges Teixeira; Júlia Zanini Campos; Caroline Isabel Kothe; Juliane Elisa Welke; Eliseu Rodrigues; Jeverson Frazzon; Roberta Cruz Silveira Thys (Food Research International, 2024)

Effects of Myrcia pubipetala Miq (Myrtaceae) extract on innate inflammatory response - Pâmela Pacassa Borges; Larissa Benvenutti; Aline Lana Schneider; Marcelo Rodrigo Franke Echterhoff; Bruna Gonçalves Lopes; Diogo Alexandre Siebert; Gustavo Amadeu Micke; Luciano Vitali; Michele Debiasi Alberton; Nara Lins Meira Quintão; José Roberto Santin; Isabel Daufenback Machado (Natural Product Research, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Prey consumption and conversion efficiency in females of two feral populations of Macrolophus pygmaeus, a biocontrol agent of Tuta absoluta - Isabel Borges; Luísa Oliveira; Francisco Barbosa; Elisabete Figueiredo; José Carlos Franco; Ana C. Durão; António Onofre Soares (Phytoparasitica, 2024)
Macrolophus pygmaeus (Rambur, 1839) (Hemiptera: Miridae) is a polyphagous predator used in programs of biological control and integrated pest management as a natural enemy against small arthropod pests including whiteflies, thrips, spider mites and aphid. This mirid is also successfully mass reared under factitious prey for commercial purposes. In the present study we assessed and compared the prey consumption, weight gain and conversion efficiency in females of two populations of M. pygmaeus , from mainland Portugal and the Azores, fed on single prey diets of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs, or Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) eggs. We found that female’s prey consumption on eggs of T. absoluta was higher than that of E. kuehniella , presumably due to the comparative size/amount of biomass of the eggs. Translating prey consumption in biomass ingested, we only found a significant difference for consumption on E. kuehniella eggs by M. pygmaeus from the Azores. Despite the smaller size of females from the Azores, they were able to consume more prey and ultimately reaching a similar body weight and conversion efficiency compared with females from mainland, independently of the prey provided. Our results are in line with a previous study, showing differences in the life-history traits of M. pygmaeus from mainland Portugal and Azorean populations fed on alternative prey. From an applied perspective, our results are a contribution to the decision-making on the use of the most effective biocontrol agents for different prey and/or agroecosystem contexts.

Genetic Analysis of LigA, LipL32, Loa22, and OmpL1 Antigens from Leptospira spp. Sejroe Serogroup: How Close We Are To a Vaccine Against Bovine Leptospirosis? - Maria Isabel Nogueira Di Azevedo; Ana Luiza dos Santos Baptista Borges; Frederico Kremer; Juliana dos Santos Loria de Melo; Filipe Anibal Carvalho-Costa; Walter Lilenbaum (Current Microbiology, 2023)

Forecasting distributional shifts of Patella spp. in the Northeast Atlantic Ocean, under climate change - Diana Freitas; Débora Borges; Francisco Arenas; Isabel Sousa Pinto; Cândida Gomes Vale (Marine Environmental Research, 2023)

How to use human biomonitoring in chemical risk assessment: Methodological aspects, recommendations, and lessons learned from HBM4EU - Tiina Santonen; Selma Mahiout; Paula Alvito; Petra Apel; Jos Bessems; Wieneke Bil; Teresa Borges; Stephan Bose-O'Reilly; Jurgen Buekers; Ana Isabel Cañas Portilla; Argelia Castaño Calvo; Mercedes de Alba González; et al. (International Journal of Hygiene and Environmental Health, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Pinnipeds carriers of pathogenic Leptospira: New data based on molecular characterization - Felipe D'Azeredo Torres; Ana Luiza dos Santos Baptista Borges; Cristiane Kolesnikovas; Camila Domit; Carla Beatriz Barbosa; Filipe Anibal Carvalho-Costa; Maria Isabel Nogueira Di Azevedo; Walter Lilenbaum (Research in Veterinary Science, 2023)

Secondary succession in swamp gallery forests along 65 fallow years after shifting cultivation - Sílvia Laine Borges; Maxmiller Cardoso Ferreira; Bruno Machado Teles Walter; Ana Carla dos Santos; Aldicir Osni Scariot; Isabel Belloni Schmidt (Forest Ecology and Management, 2023)

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Changes in land use of temperate forests associated to avocado production in Mexico: Impacts on soil properties, plant traits and insect-plant interactions - Abel Pérez-Solache; Marcela Sofía Vaca-Sánchez; Yurixhi Maldonado-López; Maurício Lopes De Faria; Magno Augusto Zazá Borges; Marcílio Fagundes; Ken Oyama; María Isabel Méndez-Solórzano; Joan Sebastian Aguilar-Peralta; Rafael Hernández-Guzmán; Pablo Cuevas-Reyes (Agricultural Systems, 2023)

Can the ladybird predator Scymnus nubilus contribute to control of the aphid Aphis frangulae, a pest threatening the Macaronesia endemic Frangula azorica? - Isabel Borges; Patrícia Arruda; Roberto Meseguer; Virgilio Vieira; Gemma Pons-Solé; António Onofre Soares (BioControl, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Habitat filtering and inferred dispersal ability condition across‐scale species turnover and rarity in Macaronesian island spider assemblages - Jagoba Malumbres‐Olarte; François Rigal; Marco Girardello; Pedro Cardoso; Luís Carlos Crespo; Isabel R. Amorim; Miquel Arnedo; Mário Boieiro; José Carlos Carvalho; Rui Carvalho; Rosalina Gabriel; Lucas Lamelas‐Lopez; et al. (Journal of Biogeography, 2021)
Aim Habitat diversity has been linked to the diversity and structure of island communities, however, little is known about patterns and processes within habitats. Here we aim to determine the contributions of habitat type and inferred dispersal frequency to the differences in taxonomic structure between assemblages in the same island habitat. Location The Macaronesian archipelagos (Azores, Madeira, the Canary Islands and Cabo Verde). Taxon Spiders (Araneae). Methods We established forest and dry habitat sites (each with five plots) on two islands per archipelago. We collected spiders using standardised sampling protocols. We tested the differences in beta diversity separately for each habitat and for each inferred category of ballooning (an aerial dispersal strategy) frequency across geographic scales through nested non‐parametric permutational multivariate analyses of variance. We then tested whether ballooning and habitat influenced heterogeneity in species composition (dispersion in beta diversity) in the two habitat types. We analysed the effects of habitat and ballooning on species abundance distribution (SAD) and rarity by fitting Gambin models and evaluating the contribution of ballooning categories to SAD. Results Communities of the same archipelago and habitat were taxonomically more similar, and beta diversity increased with geographic scale, being greater in dry habitats. There was greater species replacement among assemblages in dry habitats than in forests, with greater differences for rare ballooners. There were no differences in SAD between habitats although dry habitat sites seemed to harbour more species with low abundances (rare species) than forests. Main conclusions Habitat type does not only condition the differences between spider assemblages of the same habitat but also the scale at which they occur. These differences may be determined by the heterogeneity in the physical structure of each habitat as well as how much this structure facilitates aerial dispersal (ballooning), and should be considered in theories/hypotheses on island community assembly as well as in conservation strategies.

Invasion and Extirpation Potential of Native and Invasive Spartina Species Under Climate Change - Francisco O. Borges; Catarina P. Santos; José R. Paula; Enrique Mateos-Naranjo; Susana Redondo-Gomez; Janine Barbara Adams; Isabel Caçador; Vanessa F. Fonseca; Patrick Reis-Santos; Bernardo Duarte; Rui Rosa (Frontiers in Marine Science, 2021)
Coastal areas host some of the planet’s most productive ecosystems, providing life-sustaining ecological services and several benefits to humankind, while also being some of the most threatened areas (e.g., by globalization, climate change, and biological invasion). Salt marshes are coastal habitats with a key role in food and shelter provisioning, sediment deposition, nutrient cycling and carbon storage. Spartina spp. is a genus of grass halophytes which occurs in salt marshes worldwide, and includes species with different invasive potential. We evaluated the effect of climate change in the distribution and invasion potential of five Spartina species ( S. anglica , S. alterniflora , S. densiflora , S. patens , and S. maritima ) at a global scale. Species distribution models (SDMs) were applied on species occurrence data and atmospheric environmental predictors (WorldClim 2.1) to project potential changes in habitat suitability and associated changes in distribution and species co-occurrence until the end of the century, across four Shared Socioeconomic Pathway scenarios (i.e., SSP1-2.6 to SSP5-8.5). Projections showed a global trend for increasing species co-occurrence, with a general range expansion potentiated by increasing pathway severity. This study suggests that Spartina species can potentially benefit from climate change, predicting poleward expansions in the Northern Hemisphere for most species, with results pointing at increased conflict and invasion potential in Northern Europe and East Asian shorelines, already under strong invasive pressure. S. anglica is projected to remain a successful invader, with more severe scenarios likely favoring greater expansions. S. alterniflora exhibits very low expansion comparatively, despite exhibiting the same northward distribution shift. SSP1-2.6 produced the smallest change to species co-occurrence, suggesting a smaller potential for invasion-related conflicts, although still registering a potential net expansion for the Genus. Despite their limitations, SDMs can help establish general trends in climate change ecology and inform policymakers and environmental agents to ensure the correct management of these habitats and, ultimately, ecosystems.

What Cancer Patients Want to Know? Questions from Oncologic Patients in a Brazilian Private Cancer Center - João Marcos Cansian; Tyana Mara Ribas D’Ávila Raymundo de Oliveira; Augusto Marques Moreira; Mariana Oliveira Tripoli de Mattos; Carla Isabel Borré; Bruno Perosa Carniel; Victória da Luz Viega Borges; Marieli Barp Ziliotto; Thais Vanessa Salvador; Thaísa Hanemann; Marco Aurélio Farina Júnior; Taiana Saraiva; et al. (Journal of Cancer Education, 2021)

Technological Scenario for Masks in Patent Database During Covid-19 Pandemic - Tatianny de Araújo Andrade; José Adão Carvalho Nascimento Junior; Anamaria Mendonça Santos; Lysandro Pinto Borges; Lucindo José Quintans-Júnior; Cristiani Isabel Banderó Walker; Luiza Abrahão Frank; Mairim Russo Serafini (AAPS PharmSciTech, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Sustainable management of economically valuable seaweed stocks at the limits of their range of distribution: Ascophyllum nodosum (Phaeophyceae) and its southernmost population in Europe - Débora Borges; Rita Araujo; Isabel Azevedo; Isabel Sousa Pinto (Journal of Applied Phycology, 2020)

Seasonal fire management by traditional cattle ranchers prevents the spread of wildfire in the Brazilian Cerrado - Ludivine Eloy; Isabel Belloni Schmidt; Silvia Laine Borges; Maxmiller Cardoso Ferreira; Teomenilton A. dos Santos (Ambio, 2019)

Mapping seaweed beds using multispectral imagery retrieved by unmanned aerial vehicles - Débora Borges; Isabel Azevedo; Luís Pádua; Telmo Adão; Emanuel Peres; Joaquim Sousa; Isabel Sousa Pinto; José Gonçalves (Frontiers in Marine Science, 2019)

Assessment of spatial and seasonal biomass variation of intertidal seaweed species with commercial potential use as basis for future tailored standing stocks management - Débora Borges; Isabel Azevedo; Rosa Melo; Sara Antunes; Isabel Sousa Pinto (Frontiers in Marine Science, 2019)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Human bocavirus in hospitalized children under 5 years with acute respiratory infection, São Paulo, Brazil, 2010 - Patricia Evelin Silva; Cristina Adelaide Figueiredo; Adriana Luchs; Terezinha Maria de Paiva; Margarete Aparecida Benega Pinho; Renato Sousa Paulino; Daniela Bernardes Borges da Silva; Katia Corrêa de Oliveira Santos; Ana Maria Sardinha Afonso; Maria Isabel de Oliveira (Archives of Virology, 2018)

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Harmonia axyridis failed to establish in the Azores: the role of species richness, intraguild interactions and resource availability - António Onofre Soares; Alois Honěk; Zdenka Martinkova; Jiri Skuhrovec; Pedro Cardoso; Isabel Borges (BioControl, 2017)

Bee pollination and evidence of substitutive nectary in Anadenanthera colubrina (Leguminosae-Mimosoideae) - Laís Angélica Borges; Isabel Cristina Machado; Ariadna Valentina Lopes (Arthropod-Plant Interactions, 2017)

TRPA1, substance P, histamine and 5-hydroxytryptamine interact in an interdependent way to induce nociception - Luana Fischer; Maria Isabel Lavoranti; Mariana de Oliveira Borges; Alana Farias Miksza; Natalia Fantin Sardi; Bruno Jacson Martynhak; Claudia H. Tambeli; Carlos Amílcar Parada (Inflammation Research, 2017)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Development of an autonomous system for integrated marine monitoring - Magalhães Catarina; Mucha Ana Paula; Carvalho Maria; Ribeiro Hugo; Almeida Cristina; Azevedo Isabel; Ramos Sandra; Borges Teresa; Leandro Sérgio; Dos Santos Antonina; Silva Alexandra; Bartilotti Cátia; et al. (Frontiers in Marine Science, 2016)

Evidence for multiple founding lineages and genetic admixture in the evolution of species within an oceanic island weevil (Coleoptera, Curculionidae) super‐radiation - Christiana M. A. Faria; Antonio Machado; Isabel R. Amorim; Matthew J. G. Gage; Paulo A. V. Borges; Brent C. Emerson (Journal of Biogeography, 2016)
Aim To infer colonization and speciation history for a closely related complex of nine species within the enigmatic Canary Island Laparocerus weevil radiation of 128 species. Using molecular dating and the spatial and temporal context that islands provide, we evaluate the possible explanations of incomplete lineage sorting and gene flow for the origin of shared genetic variation among species from different islands. Location Canary Islands (Gran Canaria, Tenerife, La Palma and El Hierro). Methods We collected a total of 173 specimens from 37 sites distributed across the four islands. Phylogenetic analyses of mitochondrial ( COII ) and nuclear ( ITS 2) sequence data and molecular dating techniques were used to infer the origin of the group in the archipelago and their history of colonization and differentiation. Results Gran Canaria appeared to be the geographical origin of the complex. An unexpected result was that mt DNA revealed each of the single species on La Palma and El Hierro to be the product of more than one colonization event from more than one source island. In both cases nuclear ITS 2 data revealed these multiple colonizations to have been followed by admixture. Main conclusions The two gene trees present very different topologies, with a rather simple colonization history required to explain the pattern of nuclear gene relationships, while the mt DNA gene tree implicates a much more complex history of colonization. Explanations of incomplete lineage sorting are ruled out and a history of colonization and speciation for the L. tessellatus complex involving genetic admixture is inferred.

Effect of temperature and prey in the biology of Scymnus subvillosus - Dalila Sebastião; Isabel Borges; António Onofre Soares (BioControl, 2015)

Phylogeography and molecular phylogeny of Macaronesian island Tarphius (Coleoptera: Zopheridae): why are there so few species in the Azores? - Isabel R. Amorim; Brent C. Emerson; Paulo A. V. Borges; Robert K. Wayne (Journal of Biogeography, 2012)
Aim We used a phylogenetic framework to examine island colonization and predictions pertaining to differentiation within Macaronesian Tarphius (Insecta, Coleoptera, Zopheridae), and explain the paucity of endemics in the Azores compared with other Macaronesian archipelagos. Specifically, we test whether low diversity in the Azores could be due to recent colonization (phylogenetic lineage youth), cryptic speciation (distinct phylogenetic entities within species) or the young geological age of the archipelago. Location Macaronesian archipelagos (Azores, Madeira and the Canary Islands), northern Portugal and Morocco. Methods Phylogenetic analyses of mitochondrial and nuclear genes of Tarphius beetles of the Azores, other Macaronesian islands and neighbouring continental areas were used to investigate the origin of island biodiversity and to compare patterns of colonization and differentiation. A comparative nucleotide substitution rate test was used to select the appropriate substitution rate to infer clade divergence times. Results Madeiran and Canarian Tarphius species were found to be more closely related to each other, while Azorean taxa grouped separately. Azorean taxa showed concordance between species and phylogenetic clades, except for species that occur on multiple islands, which segregated by island of origin. Divergence time estimates revealed that Azorean Tarphius are an old group and that the most recent intra‐island speciation event on Santa Maria, the oldest island, occurred between 3.7 and 6.1 Ma. Main conclusions Our phylogenetic approach provides new evidence to understand the impoverishment of Azorean endemics: (1) Tarphius have had a long evolutionary history within the Azores, which does not support the hypothesis of fewer radiation events due to recent colonization; (2) the current taxonomy of Azorean Tarphius does not reflect common ancestry and cryptic speciation is responsible for the underestimation of endemics; (3) intra‐island differentiation in the Azores was found only in the oldest island, supporting the idea that young geological age of the archipelago limits the number of endemics; and (4) the lack of evidence for recent intra‐island diversification in Santa Maria could also explain the paucity of Azorean endemics. Phylogenetic reconstructions of other species‐rich taxa that occur on multiple Macaronesian archipelagos will reveal whether our conclusions are taxon specific, or of a more general nature.

Reproductive isolation between diploid and tetraploid cytotypes of Libidibia ferrea (= Caesalpinia ferrea) (Leguminosae): ecological and taxonomic implications - Laís Angélica Borges; Luiz Gustavo Rodrigues Souza; Marcelo Guerra; Isabel Cristina Machado; Gwilym P. Lewis; Ariadna Valentina Lopes (Plant Systematics and Evolution, 2012)

Resolving the Azorean knot: a response to Carine & Schaefer (2010) - Kostas A. Triantis; Joaquín Hortal; Isabel Amorim; Pedro Cardoso; Ana M. C. Santos; Rosalina Gabriel; Paulo A. V. Borges (Journal of Biogeography, 2012)
Carine & Schaefer ( Journal of Biogeography , 2010, 37 , 77–89) suggest that the lack of past climate oscillations in the Azores may have contributed to the low plant endemism in this archipelago compared to that of the Canary Islands, a pattern they term the Azorean diversity enigma. Here we challenge their hypothesis, and discuss how the particular characteristics of the Azores may have driven current diversification patterns in this archipelago. We argue that the restricted number of Azorean endemic species and their wide distribution is explicable by the geological, geographical and ecological attributes of the archipelago. That is, the Azores are too young, too small, and too environmentally homogeneous to have hosted many in situ diversification events, so they do not host as many endemic species as other Macaronesian archipelagos, such as Madeira and especially the Canary Islands.

Prey availability in time and space is a driving force in life history evolution of predatory insects - Isabel Borges; António Onofre Soares; Alexandra Magro; Jean-Louis Hemptinne (Evolutionary Ecology, 2011)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

Harmonia axyridis: What will stop the invader? - António Onofre Soares; Isabel Borges; Paulo A. V. Borges; Geneviève Labrie; Éric Lucas (BioControl, 2008)

Chromosome numbers and microsporogenesis in Brachiaria brizantha (Gramineae) - Andréa Beatriz Mendes-Bonato; Maria Suely Pagliarini; Fernanda Forli; Cacilda Borges do Valle; Maria Isabel de Oliveira Penteado (Euphytica, 2002)